Translation and Interpreting as a Profession: Some Proposals to Boost Entrepreneurial Competence - Muñoz-Miquel, Ana (HERMES - Journal of Language and Communication in Business, 2020)
Increasing automation and the emergence of new needs and forms of communication are triggering a redefinition of the role and work settings of translators and interpreters. For this reason, and with a view to enhancing employability, students need to be aware of the range of professional profiles they can pursue and the value they can bring to society. The aim of this paper is to put forward a series of teaching proposals aimed at promoting entrepreneurial competence. After presenting the results of an exploratory study of students’ views of the profession, it proposes some activities that are considered particularly useful for fostering entrepreneurial competences.